2018
DOI: 10.1021/acs.oprd.8b00059
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Synthesis of AMPK Activators for the Treatment of Diabetic Nephropathy: From Three Preclinical Candidates to the Investigational New Drug PF-06409577

Abstract: Indole acids 1, 2, and 3 are potent 5′-adenosine monophosphate-activated protein kinase (AMPK) activators for the potential treatment of diabetic nephropathy. Compounds 1–3 were scaled to supply material for preclinical studies, and indole 3 was selected for advancement to first-in-human clinical trials and scaled to kilogram quantities. The progression of the synthesis strategy for these AMPK activators is described, as routes were selected for efficient structure–activity relationship generation and then imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Originally the synthesis of 9 was achieved in up to 42% yield by treatment of 10 with 1,3-dibromopropane (11) in the presence of sodium hydride (NaH) or potassium tert-butoxide (KOt-Bu) in THF at 5 °C. Literature research showed that a related analogue was synthesized in >70% yield by treatment of the benzylnitrile with 11 using potassium carbonate (K 2 CO 3 ) as the base in the presence of a phase-transfer catalyst in acetone.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally the synthesis of 9 was achieved in up to 42% yield by treatment of 10 with 1,3-dibromopropane (11) in the presence of sodium hydride (NaH) or potassium tert-butoxide (KOt-Bu) in THF at 5 °C. Literature research showed that a related analogue was synthesized in >70% yield by treatment of the benzylnitrile with 11 using potassium carbonate (K 2 CO 3 ) as the base in the presence of a phase-transfer catalyst in acetone.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Boronic acid 14 or a similar boron derivative such as pinacol boronic ester 36 was designed to allow convergent access to the final product 1 via Suzuki–Miyaura cross-coupling. Although pinacol boronic ester 36 was successfully obtained via the 1,1′-bis­(diphenylphosphino)­ferrocene]­palladium­(II) dichloride [Pd­(dppf)­Cl 2 ]-catalyzed borylation of 9 with pinacolborane in the presence of potassium acetate (KOAc) in dioxane and coupled with 7 to afford the desired product 1 , there was interest in identifying a more economical set of conditions for the preparation of this key intermediate or its equivalent. Attempts to directly borylate 37 by lithiation with lithium diisopropylamide (LDA) followed by treatment with trimethylborate did not result in the desired product 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that their preparation and use in Suzuki–Miyaura reactions are well established, DEA boronic esters remain rare and underutilized in organic synthesis (Figure ). They have a tetrahedral geometry about boron through the formation of a N → B dative bond and show remarkable air stability. Although investigating this type of boronic ester for lanabecestat, we were intrigued by the low solubility in a range of low-to-moderately polar organic solvents .…”
Section: High-throughput Solubility Measurementsmentioning
confidence: 99%
“…The boronic acid or pinacol boronic ester could be used discretely or as a part of a two-step telescope from a variety of borylation reactions (Scheme ). …”
Section: Development Of a Standard Crystallization Process For Dea Bo...mentioning
confidence: 99%
“…It constitutes the core structure of many natural products and synthetic bioactive compounds exhibiting a wide array of biological activities [2][3][4][5][6], and has also found use as structural parts of material science devices [7][8][9] and chiral catalysts [10][11][12]. Recent studies have shown that the substitution at the C-3 position with electron-withdrawing groups (3-EWG-indoles) not only endows these structures with important pharmaceutical/therapeutic activities [13][14][15][16][17][18][19][20][21], but also it converts them into versatile synthetic molecular platforms in heterocyclic chemistry, such as, in dearomatization-based synthetic disconnections [22]. The catalytic asymmetric dearomatization of 3-nitroindoles constitutes an iconic example of this synthetic potential [23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%